(untitled) (Journal of the College of Basic Education, 2022)
Due to the cinema on the photographs Animation (Sinmatograve), here is the ability of cinema to express the values ​​of function through the juxtaposition of an additional two or more side-by-side institution that suggest links to certain relationships and regular in the narrative of events.Since the significance stand out in the cinema through the affiliation of the materials and specific. Therefore, the total particulate film (shots) over activated during the drafting of the technical elements and technology to reach through those particulars to the meaning of the total for the movie film through the emergence of coherence shots that carry connotations phenomenon and vestigial and the ability of the receiver to recognize the relations communicative posed shots Film to suggest a sense of hidden, so the recipient’s significant role in the understanding and interpretation of these data it receives through interdependence Film across levels of contextual and interdependence Production in order to eventually reach the goal or idea intentionality employed by maker of the artwork and it dealt with this research several chapters include a study of the production of the meaning of the segment to the Everyone in the film and the film down to a holistic understanding of the film. The borders are represented by a study research: 1 reduction objective: Study the meaning of the modes of production to the total film in the film. 2 temporal limitation: the researcher chose the period from (2008 2012) for the following reasons: A directorial vision crystallized when the embodiment of the movie film.